Actor-network theory and technology innovation : advancements and new concepts - Tatnall, Arthur (New York : Information Science Reference, 2011)
"This book provides a comprehensive look at the development of actor-network theory itself, as well as case studies of its use to assist in the explanation of various socio-technical phenomena"--Provided by publisher.
Includes bibliographical references (p. 259-288) and index.
Keywords: Diffusion of innovations; Sociology